Corporate governance after the financial crisis - Vasudev, P. M. (Cheltenham Edward Elgar, 2012)
The first decade of the new millennium was bookended by two major economic crises. The bursting of the dotcom bubble and the extended bear market of 2000 to 2002 prompted Congress to pass the Sarbanes-Oxley Act, which was directed at core aspects of corporate governance. At the end of the decade came the bursting of the housing bubble, followed by a severe credit crunch, and the worst economic downturn in decades. In response, Congress passed the Dodd-Frank Act, which changed vast swathes of financial regulation. Among these changes were a number of significant corporate governance reforms.
Includes bibliographical references and index.
Keywords: Corporate governance --Law and legislation